Estrutura do dossel e morfogênese do azevém consorciado com trevo vermelho sob intervalos de corte determinados por soma térmica - Ongaratto, Fernando (2018)
The sward structure and the morphogenesis of Italian ryegrass were studied in a mixture constituted by Tifton 85 (Cynodon spp.) oversown with Italian Ryegrass (Lolium multiflorum Lam.) and Red Clover (Trifolium pratense L.). The treatments were constituted by cutting intervals determined by different thermal sums (125, 250, 375 e 500 degrees-day (GD). The cuts were performed at the intensity of 50% of the canopy height. The evaluation of morphogenic and structural variables occurred from July to October in the years 2016/17, with experimental design of complete randomized blocks. The variables sward height, extended tiller, pseudostem and forage mass fitted to linear equations, increasing as a function of the thermal sum. The leaf: stem ratio of ryegrass was higher (2.6) in the cutting interval of 125 GD and lower (0.73) in the 500 GD interval. Tifton 85 had a higher participation (13.54%) in the lowest interval while the participation of red clover was higher (12.09%) in the larger intervals (375 e 500 GD). The leaf appearance rate (0.0080 leaf/GD), phyllochron (128.8 GD) and senescence rate (0.10 cm/GD) of ryegrass were similar at different intervals. In the cutting interval of 125 GD, the lowest elongation rate (0.06 cm/GD) and the longer elongation duration (171.6 GD) were observed. Different cutting intervals determined different leaf lifespam. Under rotational stocking method, it is recommended the use of a cutting interval of 250 degrees-day considering the efficiency of the use of the forage, leaf:stem ratio of ryegrass and participation of red clover in the canopy.